(untitled) (Revista de Investigaciones Universidad del Quindío, 2019)
This document presents the risk assessment for mass removal movements activated by precipitation processes on the Chagualá road in the department of Quindío; for which it is taken as the alignment of the methodologies developed by the National Unit for Risk and Disaster Management (UNGRD) and the Colombian Geological Service, which consist of estimating the threat by means of the scientific analysis of the parameters Hydroclimatic, geological, physical, geometric and mechanical aspects of the study area, as well as the estimation of the risk factor, through the simplified bishop method; the vulnerability determination is based on the impact matrices and by means of the information cruise the risk of slip by precipitation is evaluated. The results of the study showed that the value and variation of the rainfall intensity in the function of the return period is negligible, compared to the water sheet generated by the total annual precipitation, in addition to the risk analysis showed a High level Before a movement of mass removal considering as main affectation the blockage of the road.